Functionalized ionic liquid coatings in the Pd-catalyzed selective hydrogenation of acetylene in ethylene-rich feeds - Kremitzl, Daniel; Röhrs, Karoline; Williams, Marc B.; Schulz, Peter; Wasserscheid, Peter (Journal of Ionic Liquids, 2024)
This study explores the tuning of a Pd/Al2O3 hydrogenation catalyst for the selective removal of trace acetylene from ethylene-rich feeds by coating the catalyst with non-functionalized and functionalized ionic liquids (denoted as SCILL and Advanced SCILL materials, respectively). These materials were tested in an automated continuous hydrogenation rig converting 3300 ppm of acetylene in excess ethylene, a gas mixture mimicking a technical front-end steam cracker feed composition. While the sulfonic-acid-functionalized IL coating resulted in a highly active but very unselective catalyst converting mainly ethylene to ethane, an Advanced SCILL catalyst prepared from a nitrile-functionalized IL reduced the acetylene concentration down to less than 1 ppm, while leaving over 99% of the ethylene untouched. We also examined the potential transformations of the IL layer under reaction conditions by means of 1H NMR. Except for a ketone-functionalized IL, which was inherently labile, all tested ILs primarily underwent C2-ethylation or remained unaltered. Our findings highlight the great potential of functionalized ILs in modifying heterogeneous hydrogenation catalysts.
CRIS-Team Scopus Importer:2024-05-03
Keywords: Acetylene; Ethane; Ethylene; Hydrogenation; Ionic liquid; Pd on alumina